Guidelines for the safe investigation by drilling of landfills and contaminated land (Thomas Telford, 1993)
Promotes the use of safe working practices in the investigation of landfills and contaminated land. These guidelines are intended for use by individuals or organizations involved in the planning, specification, procurement supervision and execution of such work.
Keywords: Sanitary landfills -- Design and construction.; elektronické knihy; electronic books